Research of Active Compounds from Allii Macrostemonis Bulbus and Potential Targets against Non-Hodgkin’s Lymphoma Based on Network Pharmacology - Qiu, Xiuliang; Zhao, QiuLing; Qiu, Hongqiang; Cheng, Yu; Liu, WenBin; Yang, Lin (Current Computer - Aided Drug Design, 2024)
Background: Non-Hodgkin’s Lymphoma (NHL) is a series of lymphoid malignancies in some aggressive subtypes with unsatisfactory treatment effects. Allii Macrostemonis Bulbus (Xie Bai) is a traditional Chinese medicine with anti-cancer activities, which may potentially suppress aggressive NHL. Objective: This study tries to discover active components and targets of Xie Bai in treating NHL by network pharmacology-based approaches. Methods: Compounds and related targets of Xie Bai were collected from the Traditional Chinese Medicine Database and Analysis Platform. Target genes associated with NHL were searched by GeneCards and DisGeNET, then the overlapped targets were further analyzed by STRING tool, GO, and KEGG pathway enrichment analysis. Molecular docking was employed to verify the interaction between compounds and targets. Results: 11 bioactive compounds were successfully identified, with 30 targets that were screened out for the treatment of NHL. Functional enrichment analysis suggested that Xie Bai exerted its potential effects against NHL via pathways in cancer, such as PI3K/ AKT, p53, and MAPK signaling pathways. Molecular docking results showed that 3 active compounds (quercetin, betasitosterol, and naringenin) had good affinity with selected 6 targets (TP53, AKT1, CASP3, CCND1, HPK1, and NLRP3). Conclusion: Identifying six potential genes could accurately be docked with Xie Bai and had close interactions with NHL, which may provide insight into further research and new treatment strategy.
Keywords: non-hodgkin’s lymphoma